Design And Implementation Of Woori.Id Fashion Business In Yogyakarta - Merthya Kadya Kejora; Murwanto Sigit (International Journal of Business and Quality Research, 2024)
This research aims to identify and resolve the challenges faced by the textile company, Woori.id. The focus of this research is to review further aspects of the marketing strategy implemented to improve brand image and trust which can influence purchasing decisions. Through the analysis carried out, there are a number of steps that need to be evaluated and improved by the company. The company identified steps to strengthen branding, including ease of transactions for consumers, employee training, promotion via social media, and attractive product packaging. Woori.id is also exploring marketing strategies through influencers and social media to reach the millennial generation. High quality products are sold at affordable prices to build a strong brand image. Apart from that, Woori.id exclusives its products with limited designs and focuses on quality, unique designs, customer experience and strategic business locations in Yogyakarta.